PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA PADA SISWA KELAS II SDN GALUDRA SUMEDANG MELALUI MODEL INKUIRI TERBIMBING - Salsabila Aulia Rahma; Arrahim Arrahim; Yudi Budianti (Universitas Bhinneka PGRI, 2025)
The purpose of this study is to show how a guided inquiry learning approach is used to improve students' understanding of mathematical concepts in flat geometri. Twenty-two students from grade II of SDN Galudra Sumedang participated in this classroom action research. The planning, implementation, observation, and reflection stages were discussed in three sessions in each of the two cycles of this study. Tests, observations, interviews, and documentation are some of the data collection methods used in this study. Data analysis in this study uses quantitative and qualitative methods. The findings of the study showed that the results of cycle I to cycle II increased. The increases are as follows: a) the average score for understanding mathematical concepts increased from 64.0 to 90.0, b) classical learning completeness of understanding mathematical concepts from 64% to 95%. Thus, in grade II of SDN Galudra Sumedang, the application of guided inquiry learning model can improve students' understanding of mathematics subjects.